2010
DOI: 10.1111/j.1524-4741.2010.01038.x
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy After Neo-adjuvant Chemotherapy in Breast Cancer

Abstract: The timing of sentinel node biopsy in the setting of neo-adjuvant chemotherapy for breast cancer is controversial. Sentinel node biopsy performed after neo-adjuvant chemotherapy may save patients with a nodal response the morbidity of an axillary lymph node dissection. A retrospective review of prospectively collected data compared sentinel node biopsies performed after patients had received neo-adjuvant chemotherapy with patients who had not received neo-adjuvant chemotherapy. Demographic factors, tumor chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…However, recent studies comparing two cohorts of patients, treated and not treated prior to surgery, have not demonstrated significant differences in the rate of successful sentinel node identification or in the results of the SLNB assay. These authors concluded that it is technically feasible to identify the sentinel nodes after NSBT, and that the accuracy of SLNB remains similar to that in early cancer not susceptible to neoadjuvant therapy …”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…However, recent studies comparing two cohorts of patients, treated and not treated prior to surgery, have not demonstrated significant differences in the rate of successful sentinel node identification or in the results of the SLNB assay. These authors concluded that it is technically feasible to identify the sentinel nodes after NSBT, and that the accuracy of SLNB remains similar to that in early cancer not susceptible to neoadjuvant therapy …”
Section: Discussionmentioning
confidence: 97%
“…Although breast‐conserving surgery is the goal of the local treatment of breast cancer after NSBT, the management of the axilla is not clear. Given that the axillary status represents the most important independent prognostic factor in breast cancer, complete axillary lymphadenectomy has represented the choice of treatment, but in recent years conservative options with the sentinel node assay have been proposed …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies now have demonstrated that, in patients who are clinically node negative at diagnosis, the SN can be identified over 97% of the time with low false negative rates. 17,18 Several studies also support the view that performing the SNB after NCT allows downstaging of the axilla and results in fewer patients being subjected to full axillary node dissection (ALND), with its attendant risk of chronic lymphedema. Proponents of performing the SNB prior to NCT believe that knowledge of the state of the axilla prior to the initiation of chemotherapy is critical for prognostication.…”
Section: Timing Of the Sentinel Node Biopsy In The Neoadjuvant Settingmentioning
confidence: 92%